If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4u + 7u = 0 Combine like terms: 4u + 7u = 11u 11u = 0 Solving 11u = 0 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Divide each side by '11'. u = 0 Simplifying u = 0
| 2(x+2)+2x=84 | | 0.6688=x^2+0.5(1-x)x | | 3x^3-4x^2-7x=-2 | | 4x(x+1)-(x+1)=0 | | 10+7x= | | 8(5x-1)=3 | | 20-8x= | | 20-4x= | | y=2(0.5)+1 | | 0.58+0.28t=2.64t-1.19 | | 0.1824=x-x^2 | | 2x^2+11x=75 | | 8n+3=39 | | -x-2=1-2 | | 6x-15=6x+7 | | 5x+5-4x=13 | | 0.8(3x+4)=0.3-(x-3) | | y=10x^2+3x-2 | | 1-s=6-6-6s | | -13+4=m-10 | | -3x+7y=2 | | 2x-12=6+4x | | -36+6= | | -5+8+(-9)= | | 3t-6=4(t+4) | | 0.7(2x+8)=2.7-(x-3) | | 54p^2-5q= | | 4c-11=4c+21 | | 81=25x | | 8+x=0 | | 24-43=3(x-1)-7 | | u+8=-6 |